Relationship Of Learning Outcomes Research Methodology With The Readiness Of Students To Compose A Skripsi In The Department Of IKK UNP - Putri, Rizky Ellyana; Yulastri, Asmar (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
The purpose of the research is ti describe the learning outcomes of research methodology courses, students readiness to composes skripsi, and the relationship between study results in research methodology courses and students readiness to write skripsi. The research method uses descriptive quantitative research with a correlational approach. The research population was 110 people and a sample of 52 people from students of the IKK UNP Department using proportional random sampling technique. The date sources in the study were taken by students who had completed the research methodology course and were taking skripsi courses for the 2015 and 2016 bathces. The data collection techniques un the study were carried out, by distributing research questionnaires using a Likert scale and having tested its validity and reliability. The data analysis technique used in this study was Microsoft Office Excel and SPSS version 21.00. The results in the study show that all of the learning outcomes of the research methodology courses are in the good group, the readiness of students to compose the skripsi as a whole is in the very high group, and there is a positive and significant relationship between the two. Based on the results of the study, it can be concluded that the learning outcomes of the research methodology courses affect the level student readiness to compose a skripsi.